Analisis Pengelolaan Sarana Pembelajaran pada Kegiatan di Sentra Bahan Alam Kelompok B Paud Terpadu Al Furqan Jember - Anis Nur Hidayah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the importance of managing learning resources to support the learning process of young children, particularly in natural materials activity centers that emphasize hands-on learning experiences. This study examines the management of learning resources including planning, procurement, and maintenance in Group B at the Al Furqan Integrated Early Childhood Education Center in Jember. The study aims to provide an in depth description of the process of managing learning resources in natural materials center activities. The method used in this study is a qualitative descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation, with research subjects including the school principal, educators, and facility managers. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, and data validity was tested using source and technique triangulation. The research findings indicate that the management of learning resources has been carried out systematically and sustainably. Planning is conducted flexibly and collaboratively, adapting to the needs of the learning themes. The procurement of resources is based on the established plan, utilizing available resources—whether through purchasing or the independent creation of teaching materials. Facility maintenance is carried out routinely through periodic checks, repairs, and organized storage, involving the entire school community, including students. This research indicates that the management of learning resources at the natural materials center of Group B at the Al Furqan Integrated Early Childhood Education Center in Jember has been well-organized, structured, and capable of supporting effective learning processes while providing meaningful learning experiences for young children.
Finalisasi 23 Juni 2026_Yudi
Keywords: Sarana Pembelajaran; Sentra Bahan Alam; Facility Management; Natural Materials Center; Early Childhood Education